PENGARUH KUALITAS AUDIT, LEVERAGE, DAN PROFITABILITAS TERHADAP MANAJEMEN LABA DENGAN MODERASI UKURAN PERUSAHAAN - Erma Setiawati; Novi Nur Ifgayani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STIE Tri Dharma Nusantara, 2021)
This study aims to examine the effect of audit quality, leverage, and profitability on earnings management by moderating firm size. The population in this study are various industrial companies listed on the Indonesia Stock Exchange (BEI) 2016-2019. Sampling using purposive sampling method and obtained a sample of 96 companies. The result of this study indicate that audit quality and leverage have no effect on earnings management and firm size is unable to moderate the effect of audit quality and leverage on earnings management, Meanwhile, profitability has an effect on earnings management and firm size is able to moderate the effect of profitability on earnings management. Keywords : Earning Management; Audit Quality; Leverage; Profitability; Firm Size